Future issues in wrestling research - a sport sciences perspective - Franchini, E. (International Journal of Wrestling Science, 2021)
As the most traditional combat sport in the Olympic Games, wrestling has an enormous visibility, especially due to the high number of medals at stake. Moreover, wrestling is part of continental competitions (e.g., Pan- American Games, European Games, Asian Games, African Games) and world championships for different age groups (United World Wrestling, 2021). High-level athletes development is long-term endeavor demanding specialized professionals to provide the best approach available. Thus, the cost of this process can be quite high, and those managing sport programes need to decide where, how and when to direct the support.